EVALUATION OF THE COMPRESSIVE STRENGTH AND WATER RESISTING CAPACITIES OF LIME STABILIZED SOIL BLOCKS FOR BUILDING CLIMATE RESILIENT STRUCTURES - Mohammed, I. U; Usman, Mohammed; Shariff, Farida Ujudud (FUDMA Journal of Sciences, 2023)
The compressive strength and water resisting capacities of lime stabilised soil blocks for use in building climate resilient structures were evaluated. Good laterite material, lime of suitable chemical composition and potable water were used for mixing. Six (6) different mix proportions of soil-blocks were produced i.e., 2%, 4%, 6%, 8%, 10% and 12% lime content in laterite. The dry compressive and wet compressive strengths tests for the blocks produced were measured after the period of 1, 3, 7, 14 and 28 days. Results showed that the 2% lime has an average dry compressive strength ranging between 0.17 to 0.67 N/mm2 and no wet compressive strength was recorded due to the dissolution of the blocks in water after first day of immersion and 4% lime has an average dry compressive strength ranging from 0.71 to 1.24N/mm2 and wet compressive strength ranging from 0.76 to 0.49N/mm2 from day 1 to day 3, while day 7, 14 and 28 dissolved in water. The 6% lime has an average dry compressive strength ranging between 0.58 to 1.96 N/mm2 and wet compressive strength of 0.67 to 1.47 N/mm2. A decrease in average dry and wet compressive strengths was observed for 8%, 10% and 12% lime contents. Therefore, the 6% lime-soil mix ratio gave the highest compressive strength of 1.96 N/mm2 above the weakest average strength of 1.70 N/mm2, specified by the Federal Ministry of Works and Housing, and minimum requirements of 1.75N/mm2 by the Nigerian National Building Code.
Keywords: blocks; climate resilient; compressive strength; lime, soil; stabilization